2022
DOI: 10.3390/polym14061266
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Mechanism for Designing a Personalized Cranial Implant and Its 3D Printing Using PEEK

Abstract: The rehabilitation of the skull’s bones is a difficult process that poses a challenge to the surgical team. Due to the range of design methods and the availability of materials, the main concerns are the implant design and material selection. Mirror-image reconstruction is one of the widely used implant reconstruction techniques, but it is not a feasible option in asymmetrical regions. The ideal design approach and material should result in an implant outcome that is compact, easy to fit, resilient, and provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 68 publications
1
14
0
Order By: Relevance
“…A static load of 50N on a PEEK cranial implant with Titanium micro screws only attached at symmetrical locations across the implant-skull interface showed that von Mises stresses within the PEEK implant peaked at 8.15MPa. 26 In our study, a PEEK implant with Ti-6Al-4V fixation systems remained within range of 0.0166MPa to 0.0174MPa. This significant reduction of stress in the implant could be predominantly due to a larger surface area of the fixation plates which concentrates critical stresses away from the implant towards the plate.…”
Section: Discussionsupporting
confidence: 52%
“…A static load of 50N on a PEEK cranial implant with Titanium micro screws only attached at symmetrical locations across the implant-skull interface showed that von Mises stresses within the PEEK implant peaked at 8.15MPa. 26 In our study, a PEEK implant with Ti-6Al-4V fixation systems remained within range of 0.0166MPa to 0.0174MPa. This significant reduction of stress in the implant could be predominantly due to a larger surface area of the fixation plates which concentrates critical stresses away from the implant towards the plate.…”
Section: Discussionsupporting
confidence: 52%
“…Meta-analyses performed by Punchak et al and van de Vijfeijken proved that surgeries performed with the use of PEEK carry lower risks of infection than PMMA and autologous bone cranioplasties [ 106 , 191 ]. In a study performed by Mian et al, 3D-printed PEEK implants delivered great precision, minimal deviation (0.5919 mm), with maximal von Mises stress (8.15 MPa), von Mises strain (0.002) and minimal deformation (0.18 mm), which underlines the implant’s extraordinary load-bearing capability [ 192 ]. Similar observations have been made in a preclinical study designed by Sharma et al [ 193 ].…”
Section: 3d Cranioplastymentioning
confidence: 99%
“…Modern 3D computer-assisted surgery (3D CAS), which combines 3D printing technology with 3D imaging techniques, has undergone remarkable developments in the past decades. As shown in Figure 2 , several protocols are essential to 3D CAS: 1) information acquisition, 2) planning, 3) virtual operation, 4) 3D printing, and 5) surgery and postoperative analysis ( Troulis et al, 2002 ; Prevost et al, 2019 ; Mian et al, 2022 ). Although potential errors occur in the fabrication of customized barrier membranes after tomography data acquisition, image processing, and 3D fabrication ( Tian et al, 2021 ), technological developments in rapid prototyping systems have considerably contributed to the accurate and detailed replication of craniofacial devices ( Sharma et al, 2021 ).…”
Section: Protocols and Advantages Of Modern 3d Computer-assisted Surgerymentioning
confidence: 99%